Salutogenic Environmental Health Model—proposing an integrative and interdisciplinary lens on the genesis of health - Pleyer, Jule Anna; Pesliak, Laura Dominique; Malsch, Annette Konstanze Fides; McCall, Timothy (Frontiers in Public Health, 2024)
Introduction The maintenance of health is a central objective of public health initiatives. Within the salutogenic paradigm, health promotion is focused on understanding the mechanisms of health development. Models serve as indispensable tools. One of the leading paradigms in the health sciences is the Salutogenic Model developed by Aaron Antonovsky. However, it lacks sufficient specification to reflect the complexity of the environmental dimensions that have emerged from research in environmental health science. The interactions and impact pathways between these dimensions on health status are not adequately distinguished. The objective of this study is to address this gap by extending Antonovsky’s model to encompass environmental dimensions, that is, the interactions between humans and their environment. Furthermore, the study will integrate examples of models and theories from various disciplines to illustrate how a more comprehensive and holistic explanation of health development can be provided from an interdisciplinary environmental public health perspective. Methodology As part of a three-step approach, a Basic Model was first developed that integrates the five environmental dimensions—Natural, Built-Material, Socio-Cultural, Psycho-Social, and Individual—into the Salutogenic Model. Subsequently, narrative non-exhaustive literature research was used to identify interdisciplinary example models. The models were used to identify gaps in the Basic Model through a critical lens and to synthesize them into a more holistic model. Results The synthesis of fifteen interdisciplinary models resulted in the development of an integrative Salutogenic Environmental Health Model (SEHM), which comprises twelve principal components of health development and their interactions and pathways. Links to the original models permit the user to refer back to them. Discussion This integrative approach offers a comprehensive understanding of the development of health by synthesizing disparate explanatory models and theories from various disciplines through theoretical analysis. The various environmental dimensions and the determinants of health contained therein, as well as their mental and physical processing and the associated components of health development and their interactions, are summarized in this new model. The SEHM thus enables a differentiated analysis of health determinants and serves as an operational framework for health promotion and pathways to well-being in contemporary research contexts.